Risk of bacterial infections in patients with sickle cell disease: an integrative literature review (Research, Society and Development, 2025)
This study aimed to identify the main factors involved in the increased risk of bacterial infections in patients with sickle cell disease. This is an integrative literature review conducted from May to July 2025. The search was carried out in the BVS, PubMed, ScienceDirect, Scopus, and Web of Science databases, including articles published between 2020 and 2025. The results identified splenic dysfunction as one of the main susceptibility factors to infections in patients with sickle cell disease, in addition to socioeconomic issues and risky behaviors involving environmental exposure, such as pica syndrome. Encapsulated microorganisms, such as Streptococcus pneumoniae, Haemophilus influenzae, and Neisseria meningitidis, are the most frequent agents. The most effective preventive measures include vaccination, antibiotic prophylaxis, and health education. However, challenges remain, especially in low- and middle-income countries. It is concluded that early interventions, effective public policies, and consistent follow-up are essential to reduce morbidity and mortality associated with infections in the sickle cell population.